Pluggable semimetal-based non-sacrificial electrode and application thereof

The pluggable semi-metal-based non-sacrificial electrode prepared by using halogen atom-doped C3N4@C(CN)3-based catalyst in plant batteries was solved, and the problems of copper-zinc electrode corrosion and zinc ion contamination were improved, and the stability of the battery was improved. and power density, achieving more efficient power conversion.

CN119324231AActive Publication Date: 2025-01-17NANJING UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411361499.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-17
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The copper and zinc electrodes used in existing plant batteries are prone to corrosion during the reaction, resulting in unstable currents, and the entry of zinc ions into the plants may lead to poisoning, limiting their application, and the output voltage and current are not sufficient to meet conventional needs.

Method used

Plugable semi-metal-based non-sacrificial electrode prepared on porous stainless steel substrate using halogen atom-doped C3N4@C(CN)3-based catalyst, has excellent redox capability and carrier separation and transmission through in-situ polymerization loading. Ability to avoid electrode decomposition and improve battery stability and life.

Benefits of technology

It significantly improves the stability and life of plant batteries, improves the catalytic power supply capacity of the battery, enhances carrier transmission, reduces charge transmission resistance, improves the power density of the battery, and avoids zinc ion contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324231A_ABST
    Figure CN119324231A_ABST
Patent Text Reader

Abstract

The invention discloses a pluggable semimetal-based non-sacrificial electrode and application thereof, the electrode is prepared by taking halogen atom doped semimetal-based C3N4C (CN) 3 as a catalytic material, and attaching the catalytic material to a porous stainless steel conductive substrate in situ through high-temperature copolymerization. The semimetal-based non-sacrificial electrode has relatively strong acid and alkali corrosion resistance, thermal stability and carrier migration and separation capability, and the oxidation-reduction capability of the semimetal-based non-sacrificial electrode catalytic material can be further optimized by adjusting the doping type and proportion of halogen atoms; the method can be applied to oxidation reduction of electrolytes in plants and in-vivo plant power generation and supply output.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage and energy conversion, and specifically relates to an organic semi-metal-based catalytic material and a pluggable electrode device thereof. Technical Background

[0002] Technologies that use clean energy to generate electricity, such as wind power and solar power, are generally energy-saving and environmentally friendly, but these power generation technologies and equipment are expensive, highly dependent on geographical locations, and are easily affected by climate, and need to be improved. The demand for electricity acquisition in future social development can be summarized as "safe, efficient, sustainable, and low-cost", which is also the unchanging pursuit of energy development. Plant power supply technology is a green energy technology that uses plants as the main power supply body and uses electrochemical means and the plant's own physiological processes to directly or indirectly convert light energy, mechanical energy, and biomass energy in nature into electrical energy. It can provide green, environmentally friendly, resource-rich, and long-life clean energy, and shows important application prospects in many fields.

[0003] In recent years, researchers at home and abroad have conducted preliminary explorations in the field of plant power generation, including sacrificial electrode plant primary battery power generation technology, photosynthesis-like power generation technology, plant microbial fuel cell power generation technology, and plant regional ion concentration disturbance power generation technology. Electricity can be extracted from the stems and leaves of lemons, potatoes, plantains, moss leaves, aloe vera, pineapples, tomatoes, lemons, rice grass, money trees, and silver poplars, with a maximum output power of 100mW / m 2 , the longest power supply time can be up to 5 months, the maximum open circuit voltage is 30.6V, the maximum current is generally at the microampere level, and the load resistance is in tens of ohms. However, the output voltage and current provided by these current plant batteries and their technologies are relatively small, the power supply capacity is relatively limited, and the battery life and power density are difficult to meet conventional needs. In particular, the electrodes currently used in plant batteries are copper and zinc. During the electrode reaction process, the electrode surface will react with the plant tissue fluid, and the zinc electrode will be gradually corroded. The consumption of the electrode or the passivation of the surface will affect the sustainable and stable output of the current, and even cause the battery to have no current output; during the electrode reaction process, zinc ions will continue to dissolve and enter the plant body. If zinc ions continue to accumulate in the plant body, it may cause plant poisoning, limiting its practical application.

[0004] Organic polymers have the advantages of low toxicity, good biocompatibility and easy modification and regulation, and show good application potential in the biomedical field. As a typical organic polymer material, semimetallic C(CN)3 has been synthesized in recent years and used in the field of photoelectrocatalysis. The total number of valence electrons in C(CN)3 is an odd number, so spontaneous magnetization occurs. The magnetic moment is distributed between three adjacent N atoms, and N atoms have smaller and more localized p orbitals than C atoms. The p orbitals of C atoms at the joints of the molecular structure promote ferromagnetic coupling. Integer magnetic moment and ferromagnetism make C(CN)3 based on the triazine ring structure an intrinsic semimetal. The narrow band gap width determines the excellent conductivity of C(CN)3, but its intrinsic redox ability is suppressed. Therefore, it is necessary to regulate the band structure of C(CN)3 by heteroatom and heterocomponent doping modification, so as to achieve the purpose of optimizing its catalytic performance. Summary of the invention

[0005] The purpose of the present invention is to provide a pluggable semi-metallic non-sacrificial electrode and its application in plant batteries. The preparation process of the semi-metallic pluggable catalytic electrode is controllable, and it has strong acid and alkali corrosion resistance and high thermal stability, especially its excellent redox ability and carrier separation and transmission ability, so that the electrode has the ability to catalytically generate electricity in the plant body.

[0006] The technical solution to achieve the purpose of the present invention is:

[0007] In a first aspect, the present invention provides a pluggable semi-metal-based non-sacrificial electrode, which is formed by in-situ polymerization of a halogen-doped C3N4@C(CN)3-based catalyst on a porous stainless steel substrate, wherein the halogen atom content in the catalyst is 0.08-2wt%, and the catalyst loading on the porous stainless steel substrate is 0.5-5mg / cm 2 .

[0008] In a second aspect, the present invention further provides a method for preparing the pluggable semi-metal-based non-sacrificial electrode according to the first aspect, the specific steps of which are:

[0009] Step a), dispersing tricyanomethanated imidazolium ionic liquid, dicyandiamide and ammonium halide as raw materials in deionized water, ultrasonically treating for 10 to 30 minutes, adding a porous stainless steel substrate and soaking for 0.5 to 2 hours, evaporating the water phase, and obtaining a stainless steel electrode with a catalyst precursor attached;

[0010] Step b), heating the stainless steel electrode attached with the catalyst precursor obtained in step a) to 400-450° C. in a tube furnace at a certain heating rate, maintaining for 1-2 hours, then heating to 500-550° C., heating for 2-4 hours, naturally cooling to room temperature, washing with deionized water, and vacuum drying to obtain a pluggable semi-metal-based non-sacrificial electrode.

[0011] Furthermore, the tricyanomethanated imidazolium ionic liquid is one of tricyanomethanated 1-ethyl-3-methylimidazole, tricyanomethanated 1-propyl-3-methylimidazole, tricyanomethanated 1-butyl-3-methylimidazole, and tricyanomethanated 1-pentyl-3-methylimidazole.

[0012] Furthermore, the ammonium halide salt is one of ammonium bromide and ammonium iodide.

[0013] Furthermore, the molar ratio of the tricyanomethanated imidazolium ionic liquid to dicyandiamide is 1:10 to 1:30.

[0014] Furthermore, the molar ratio of the tricyanomethanated imidazolium ionic liquid to the ammonium halide salt is 1:1 to 1:5.

[0015] Furthermore, the heating rate is 2°C / min to 5°C / min.

[0016] In a third aspect, the present invention further provides the use of the pluggable semi-metal-based non-sacrificial electrode described in the first aspect in a plant battery.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) Unlike traditional sacrificial electrodes such as Cu and Zn used to generate electricity in plants, the present invention uses the redox ability of the carbon-based catalytic material itself to drive the redox reaction of electrolyte ions in the plant body to generate electricity for the load. The semi-metal-based catalytic material will not decompose during the power generation process, which significantly improves the stability and life of the sacrificial electrode type plant battery.

[0019] (2) Organic semimetallic C(CN)3 materials not only have high electrical conductivity and large delocalized electron density, which is conducive to carrier transport, but C(CN)3 also has good catalytic ability, which can promote the redox reaction of electrolytes in plants and generate electricity to the outside.

[0020] (3) C3N4 and C(CN)3 have similar structures, excellent compatibility and bonding strength, and outstanding interface performance, which can effectively reduce the charge transmission resistance between the two materials and improve the separation ability of photogenerated electrons and holes. Halogen atoms are embedded in the conjugated system composed of C(CN)3 and C3N4 through covalent bonds. Halogen atom doping can further adjust the band structure and conductivity of semi-metallic materials and improve the catalytic power generation capacity of non-sacrificial electrodes.

[0021] The present invention is further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1This is the preparation flow chart of halogen-doped C3N4@C(CN)3 catalytic electrode.

[0023] Figure 2 These are the SEM and EDS elemental analysis photos of the C3N4@C(CN)3@Br composite catalyst obtained in Example 2.

[0024] Figure 3 This is the XRD diffraction spectrum of the C3N4@C(CN)3@Br composite catalyst obtained in Example 2.

[0025] Figure 4 Evaluation of the acid-base stability of the C3N4@C(CN)3@Br-based non-sacrificial electrode obtained in Example 2.

[0026] Figure 5 This is the C3N4@C(CN)3@Br based non-sacrificial electrode in vivo plant battery obtained in Example 2.

[0027] Figure 6 This is the series power density curve of the C3N4@C(CN)3@Br-based non-sacrificial electrode obtained in Example 2.

[0028] Figure 7 This is the parallel power density curve of the C3N4@C(CN)3@Br-based non-sacrificial electrode obtained in Example 2. DETAILED DESCRIPTION

[0029] The following embodiments can enable those skilled in the art to more fully understand the present invention.

[0030] Example 1

[0031] 0.21 g (2.5 mmol) of dicyandiamide, 0.046 g (0.2 mmol) of tricyanomethanated 1-ethyl-3-methylimidazole and 0.02 g (0.2 mmol) of NH4Br were added to 10 ml of deionized water, and ultrasonicated and stirred for 30 min to mix evenly. 2 ) was soaked for 0.5h, and the water phase was evaporated to obtain a stainless steel electrode with a catalyst precursor attached. The stainless steel electrode loaded with the catalyst precursor was heated to 400°C at 2°C / min in a tube furnace, maintained for 1h, then heated to 550°C, maintained for 2h, naturally cooled to room temperature, washed with deionized water, and vacuum dried to obtain a pluggable semi-metal-based non-sacrificial electrode. The preparation process is shown in Figure 1 .

[0032] Three pairs of C3N4@C(CN)3@Br electrodes prepared in Example 1 were inserted into the taro in series. When the external load resistance was 6 kΩ, the maximum power density that could be achieved was 15.53 mW / m 2In the case of parallel connection, when the external load resistance is 5kΩ, the maximum power density that can be achieved is 32.36mW / m 2 .

[0033] Example 2

[0034] 0.21g (2.5mmol) of dicyandiamide, 0.046g (0.2mmol) of tricyanomethanated 1-ethyl-3-methylimidazole and 0.04g (0.4mmol) of NH4Br were added to 10ml of deionized water, and ultrasonicated and stirred for 30min to mix evenly. Add the cut porous stainless steel substrate and soak for 0.5h, evaporate the water phase to obtain a stainless steel electrode attached with a catalyst precursor. The stainless steel electrode loaded with the catalyst precursor was heated to 400℃ at 2℃ / min in a tube furnace, maintained for 1h, then heated to 550℃, kept warm for 2h, cooled naturally to room temperature, washed with deionized water, and vacuum dried to obtain a pluggable semi-metal-based non-sacrificial electrode.

[0035] Figure 2 The SEM and EDS element distribution photos of the C3N4@C(CN)3@Br electrode catalyst of Example 2 show that the material has a two-dimensional nanosheet structure and the distribution of carbon, nitrogen, oxygen and bromine elements is relatively uniform.

[0036] Figure 3 The XRD diffraction spectrum of the C3N4@C(CN)3@Br electrode catalyst of Example 2 shows two diffraction peaks at 12.8° and 27.6°, which are respectively attributed to the (100) and (002) crystal planes. The diffraction peaks of the composite materials doped with different proportions of Br are basically consistent with those of C3N4@C(CN)3 before doping, proving that the doping of halogen atoms does not change the crystal structure of the material, but replaces some of the organic skeleton atoms.

[0037] Figure 4 This is an evaluation of the acid-base stability of the C3N4@C(CN)3@Br electrode of Example 2. As can be seen from the figure, after the electrode was immersed in 1M sodium hydroxide and 1M hydrochloric acid for 6 hours, there was no catalytic material falling off in the solution, and the catalyst could still be stably attached to the electrode.

[0038] Figure 5 This is an in vivo plant battery of Zanthoxylum bungeana based on the C3N4@C(CN)3@Br electrode of Example 2.

[0039] Figure 6The power density of the plant under different external resistances when three pairs of C3N4@C(CN)3@Br electrodes of Example 2 are inserted into the taro in series. It can be seen from the figure that as the external resistance increases, the power density gradually increases. When the external load resistance is 6 kΩ, the maximum power density reached is 19.53 mW / m 2 , and then decreased to 9.21mW / m 2 about.

[0040] Figure 7 The power density of the plant under different external resistances is shown in the figure when three pairs of C3N4@C(CN)3@Br electrodes of Example 2 are inserted into the taro in parallel. As can be seen from the figure, the power density gradually increases with the increase of external resistance. When the external load resistance is 2kΩ, the maximum power density is 35.35mW / m 2 , and then decreased to 6.47mW / m 2 about.

[0041] Example 3

[0042] 0.21g (2.5mmol) dicyandiamide, 0.046g (0.2mmol) tricyanomethanated 1-ethyl-3-methylimidazole and 0.029g (0.2mmol) NH4I were added to 10ml deionized water, ultrasonicated, and stirred for 30min to mix evenly. Add the cut porous stainless steel substrate and soak for 0.5h, evaporate the water phase to obtain a stainless steel electrode attached with a catalyst precursor. The stainless steel electrode loaded with the catalyst precursor was heated to 400℃ in a tube furnace at 5℃ / min, maintained for 1h, then heated to 550℃, kept warm for 2h, cooled naturally to room temperature, washed with deionized water, and vacuum dried to obtain a pluggable semi-metallic non-sacrificial electrode.

[0043] Three pairs of C3N4@C(CN)3@Br electrodes prepared in Example 3 were inserted into the succulent. When the external load resistance was 2 kΩ, the maximum power density that could be achieved was 60.32 mW / m 2 In the case of parallel connection, when the external load resistance is 4kΩ, the maximum power density that can be achieved is 50.25mW / m 2 .

[0044] Example 4

[0045] 0.21g (2.5mmol) of dicyandiamide, 0.046g (0.2mmol) of tricyanomethanated 1-ethyl-3-methylimidazole and 0.04g (0.4mmol) of NH4Br were added to 10ml of deionized water, and ultrasonicated and stirred for 30min to mix evenly. The cut porous stainless steel substrate was added and soaked for 2h, and the water phase was evaporated to obtain a stainless steel electrode attached with a catalyst precursor. The stainless steel electrode loaded with the catalyst precursor was heated to 400℃ at 2℃ / min in a tube furnace, maintained for 2h, and then heated to 550℃, maintained for 2h, cooled naturally to room temperature, washed with deionized water, and vacuum dried to obtain a pluggable semi-metal-based non-sacrificial electrode.

[0046] Three pairs of C3N4@C(CN)3@Br electrodes prepared in Example 4 were inserted into the succulent. When the external load resistance was 1 kΩ, the maximum power density that could be achieved was 95.25 mW / m 2 In the case of parallel connection, when the external load resistance is 1kΩ, the maximum power density that can be achieved is 126.28mW / m 2 .

[0047] Example 5

[0048] 0.21g (2.5mmol) dicyandiamide, 0.046g (0.2mmol) tricyanomethanated 1-ethyl-3-methylimidazole and 0.029g (0.2mmol) NH4I were added to 10ml deionized water, ultrasonicated, and stirred for 30min to mix evenly. Add the cut porous stainless steel substrate and soak for 0.5h, evaporate the water phase to obtain a stainless steel electrode attached with a catalyst precursor. The stainless steel electrode loaded with the catalyst precursor was heated to 420℃ in a tube furnace at 5℃ / min, maintained for 1h, then heated to 500℃, kept warm for 2h, cooled naturally to room temperature, washed with deionized water, and vacuum dried to obtain a pluggable semi-metallic non-sacrificial electrode.

[0049] Three pairs of C3N4@C(CN)3@Br electrodes prepared in Example 5 were inserted into the taro in series. When the external load resistance was 2 kΩ, the maximum power density that could be achieved was 105.23 mW / m 2 In the case of parallel connection, when the external load resistance is 5kΩ, the maximum power density that can be achieved is 146.25mW / m 2 .

Claims

1. A pluggable semi-metal-based non-sacrificial electrode, characterized in that: The electrode is made of a halogen atom-doped C3N4@C(CN)3-based catalyst loaded on a porous stainless steel substrate by in-situ polymerization, wherein the halogen atom content in the catalyst is 0.08-2wt%, and the loading amount of the catalyst on the porous stainless steel substrate is 0.5-5mg / cm 2 .

2. The method for preparing a pluggable semi-metal-based non-sacrificial electrode according to claim 1, characterized in that: The specific steps are: Step a), dispersing tricyanomethanated imidazolium ionic liquid, dicyandiamide and ammonium halide as raw materials in deionized water, ultrasonically treating for 10 to 30 minutes, adding a porous stainless steel substrate and soaking for 0.5 to 2 hours, evaporating the water phase, and obtaining a stainless steel electrode with a catalyst precursor attached; Step b), heating the stainless steel electrode attached with the catalyst precursor obtained in step a) to 400-450° C. in a tube furnace at a certain heating rate, maintaining for 1-2 hours, then heating to 500-550° C., heating for 2-4 hours, naturally cooling to room temperature, washing with deionized water, and vacuum drying to obtain a pluggable semi-metal-based non-sacrificial electrode.

3. The method according to claim 2, characterized in that The tricyanomethanated imidazolium ionic liquid is one of tricyanomethanated 1-ethyl-3-methylimidazole, tricyanomethanated 1-propyl-3-methylimidazole, tricyanomethanated 1-butyl-3-methylimidazole and tricyanomethanated 1-pentyl-3-methylimidazole.

4. The method according to claim 2, characterized in that The ammonium halide salt is one of ammonium bromide and ammonium iodide.

5. The method according to claim 2, characterized in that The molar ratio of the tricyanomethanated imidazolium ionic liquid to dicyandiamide is 1:10 to 1:

30.

6. The method according to claim 2, characterized in that The molar ratio of the tricyanomethanated imidazolium ionic liquid to the ammonium halide salt is 1:1 to 1:

5.

7. The method according to claim 2, characterized in that The heating rate is 2℃ / min~5℃ / min.

8. Use of the pluggable semi-metal-based non-sacrificial electrode as claimed in claim 1 in plant batteries.

Citation Information

Patent Citations

  • Semi-metallic C4N3 nano-plate and preparation method and application thereof

    CN109012727A

  • Carbon nitride-based nickel-gold bimetallic supported catalyst and preparation method thereof

    CN111359652A

  • Supported ionic liquid nano-metal catalyst as well as preparation method and application thereof

    CN115608414A

  • Method for electrodepositing gold and synchronously regenerating iodine by using imidazole dicyandiamide ion liquid

    CN117626368A

  • Use of Supported Ionic Liquid Phase (SILP) catalyst systems in the hydroformylation of olefin-containing mixtures to aldehyde mixtures with a high proportion of 2-position unbranched aldehydes

    DE102010041821A1